1986
DOI: 10.1159/000180568
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Resistance to 1,25-Dihydroxyvitamin D: Clinical and Radiological Improvement during High-Dose Oral Calcium Therapy

Abstract: A 6-year-old boy, of consanguinous parents, presented with severe rickets and alopecia; he was found to have hypocalcaemia and elevated circulating 1,25-dihydroxyvita-min D [1,25-(OH)2D] levels. He showed no calcaemic response to 1,25-(OH)2D3 or ergocalciferol given for 3 or more months in daily doses as high as 48 µg and 6 × 106 IU, respectively. Analyses with cultured skin fibroblasts revealed a normal capacity and affinity for 1,25-(OH)2D3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…12,68 Oral calcium alone has sometimes been successfully used as a therapy for HVDRR patients from the outset. [10][11][12]69 In one study calcium delivered via the enteral route using a gastric tube was successful in reversing the metabolic abnormalities in a case of HVDRR when maintaining an IV became problematic in a young child due to repeated infections of the intravenous line. 70 A recent study has suggested the use of Cinacalcet as an adjunctive therapy for treatment of the secondary hyperparathyroidism in HVDRR.…”
Section: Treatment Of Hvdrrmentioning
confidence: 99%
“…12,68 Oral calcium alone has sometimes been successfully used as a therapy for HVDRR patients from the outset. [10][11][12]69 In one study calcium delivered via the enteral route using a gastric tube was successful in reversing the metabolic abnormalities in a case of HVDRR when maintaining an IV became problematic in a young child due to repeated infections of the intravenous line. 70 A recent study has suggested the use of Cinacalcet as an adjunctive therapy for treatment of the secondary hyperparathyroidism in HVDRR.…”
Section: Treatment Of Hvdrrmentioning
confidence: 99%
“…Once the child is older, perhaps when the skeleton has finished major growth, oral calcium often suffices to maintain normocalcemia and the IV calcium regimen can be discontinued [28]. Oral calcium alone has sometimes been successfully used as a therapy for HVDRR patients [57]. Spontaneous healing of rickets has been observed in some HVDRR patients as they get older and all therapy sometimes can be discontinued [11,26,27].…”
Section: Therapy Of Hvdrrmentioning
confidence: 99%
“…Slow disappearance of radiological changes in bones in line with normalization of other laboratory findings is in favour of diagnosis of vitamin D –dependent rickets type II. The other authors (11, 12) stated that the changes in bones were not that much visible in cases with this form of rickets (because the cases were diagnosed earlier) and these changes starter to disappear faster (after the second month) after use of the corresponding therapy.…”
Section: Discussionmentioning
confidence: 99%